THE INFLUENCE OF LEADERSHIP STYLE AND RGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Safitri, Dina; Fauzi, Achmad; Rumanta, Maman (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The purpose of this study was to determine the influence of leadership style and organizational culture on employee performance with job satisfaction as an intervening variable at the Cilegon City Food and Agriculture Security Agency. The population in this study were all employees of the Cilegon City Food and Agriculture Service. The sampling technique in this study was the saturated sampling technique, where the entire population was used as a research sample (census sample), so the sample size used in this study was 100 respondents. The research will be tested using the Partial Least Squares (PLS) analysis tool. PLS can also be used to explain whether there is a relationship between latent variables and to analyze constructs formed with reflective and formative indicators. Based on the research results, the following conclusions can be drawn: 1) Leadership style has a positive and significant effect on employee job satisfaction; 2) Work culture has a positive and significant effect on employee job satisfaction; 3) Leadership style has a positive and significant effect on employee job performance; 4) Work culture has a positive and significant effect on employee job satisfaction; 5) Job satisfaction has a positive and significant effect on employee performance; and 6) Job satisfaction can mediate between the variables of leadership style and work culture on employee performance variables.